Vaccine Diplomacy of the United States, China, India, and Russia During the COVID-19 Pandemic: A Comparative Analysis - Aleksa Filipović (Međunarodna politika, 2024)
This research strives to present a comparative analysis of the vaccine diplomacy of the United States, China, India, and Russia during the COVID19 pandemic. As each of the examined countries possesses the technology to research and manufacture the vaccines, as well as the logistical capacity and infrastructure for their global distribution, it was natural to expect that they would start with their own vaccine diplomacy, especially in the countries and regions that are considered a priority for their national and foreign policy interests. However, each country had a different approach to the vaccine diplomacy engagement based on their vaccine manufacturing capacity and global distribution limitations. At the same time, competition was observed between the rival powers. It can be concluded that although even such a severe global crisis as the COVID-19 pandemic failed to bring closer cooperation between the great powers, such a crisis established vaccine diplomacy as an additional element of foreign policy, and it will most likely be developed as a soft-power tool even more in the near future.